2022
DOI: 10.1111/and.14491
|View full text |Cite
|
Sign up to set email alerts
|

Silymarin abrogates acrylamide‐induced oxidative stress‐mediated testicular toxicity via modulation of antioxidant mechanism, DNA damage, endocrine deficit and sperm quality in rats

Abstract: Acrylamide (ACR) is a toxic chemical formed in foods processed at high temperature; it is a food‐borne toxicant with increasing public health attention due to its carcinogenic, neurotoxic and reproductive toxicities. However, till date, it is unknown whether silymarin (SIL) could attenuate ACR testicular toxicity. Therefore, the present study investigated the effect of SIL on ACR testiculotoxicity in rats. Rats were randomly divided and administered respective agents in Control group, ACR group, SIL group and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 50 publications
1
10
0
Order By: Relevance
“…It was observed in the DM group that T, LH, and FSH serum levels prominently reduced in comparison to control (Table 4). The depressed levels of these reproductive hormones suggest deficits in testicular testosterone synthesis which can be endocrinologically associated with dysregulations in the gonadotrophic hormones found in this study [34]. Furthermore, insulin resistance, as observed in the DM rats has been linked to reduced secretion of T by Leydig cells [7].…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…It was observed in the DM group that T, LH, and FSH serum levels prominently reduced in comparison to control (Table 4). The depressed levels of these reproductive hormones suggest deficits in testicular testosterone synthesis which can be endocrinologically associated with dysregulations in the gonadotrophic hormones found in this study [34]. Furthermore, insulin resistance, as observed in the DM rats has been linked to reduced secretion of T by Leydig cells [7].…”
Section: Discussionsupporting
confidence: 50%
“…The technique of Evans and Maxwell [33] was adopted for sperm abnormality study. Whereas, the assessment of sperm motility was done according to Morrissey et al (1988) as stated in our recent paper by Alturki et al [34].…”
Section: Determination Of Sperm Count Motility Andmentioning
confidence: 99%
See 1 more Smart Citation
“…29 It has been reported by many studies that ACR causes organ toxicities. 4 This study revealed that NA administration reduced ACRinduced testicular toxicity in rats.…”
Section: Discussionmentioning
confidence: 75%
“…ACR occurs more often in foods of vegetable origin (such as potatoes, cereals, coconut, lentils, and asparagus) rich in these substances 3 . Studies have shown that the administration of 50 mg/kg ACR to male rats for 14 days has a genotoxic effect 4 . In another study, it was determined that 5 mg/kg ACR administration to rats weighing 120–150 g for 4 weeks had effects such as a decrease in testosterone level and Leydig cell numbers, apoptosis in testicular cells, causing giant cells, and delaying cell cycle in the body 5 .…”
Section: Introductionmentioning
confidence: 99%